2016
DOI: 10.3390/molecules21111530
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry and Pharmacology of Citrus Limonoids

Abstract: Citrus limonoids (CLs) are a group of highly oxygenated terpenoid secondary metabolites found mostly in the seeds, fruits and peel tissues of citrus fruits such as lemons, limes, oranges, pumellos, grapefruits, bergamots, and mandarins. Represented by limonin, the aglycones and glycosides of CLs have shown to display numerous pharmacological activities including anticancer, antimicrobial, antioxidant, antidiabetic and insecticidal among others. In this review, the chemistry and pharmacology of CLs are systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 187 publications
(374 reference statements)
2
99
0
2
Order By: Relevance
“…They mainly occur in citrus fruits, including lemons, in which they are found mainly in the seeds, pulp, and peel. There are predominantly two such compounds in C. limon fruits-limonin and nomilin ( Figure 3) [37]. Studies have shown that the concentrations of the compounds of this group are dependent on fruit growth and maturation stages.…”
Section: Chemical Composition Of C Limonmentioning
confidence: 99%
“…They mainly occur in citrus fruits, including lemons, in which they are found mainly in the seeds, pulp, and peel. There are predominantly two such compounds in C. limon fruits-limonin and nomilin ( Figure 3) [37]. Studies have shown that the concentrations of the compounds of this group are dependent on fruit growth and maturation stages.…”
Section: Chemical Composition Of C Limonmentioning
confidence: 99%
“…Aside from polyphenols, limonoids and adrenergic amines (mainly synephrine) are also found in mandarins (Ye and others ). Limonoids are plant alkaloids, modified triterpene glucoside derivatives occurring in mature citrus fruit tissues and seeds (Gualdani and others ). Significant variation in limonoid content was reported in 9 studied mandarin cultivars, where values ranged from 105 to 1128 μg/g DW (Ye and others ).…”
Section: Nutritional Value and Health Benefits Of Mandarins And Derivmentioning
confidence: 99%
“…Limonoids are tetranortriterpenoids found in Citrus seeds, pulp, and peels, known as bitter compounds [51]. According to their polarity, limonoids aglycones occur mostly in Citrus peel, while glycoside forms are most abundant in pulp [19]. All compounds were tentatively identified by comparison of their elution order, UV, full MS, and fragmentation pattern (MS/MS) data (Table 6) with those reported in the literature.…”
Section: Legal Quality Parametersmentioning
confidence: 99%
“…Thus, compound 3 was tentatively identified as limonexic acid or its constitutional isomer isolimonexic acid [55]. Compounds 5 (tR = 41.7 min) and 7 (tR = 43.2 min) had the same molecular weight 546 u and superimposable fragmentation pathways with ions at m/z 501, 457 and 397 generated by the successive losses of two CO2 molecules and an acetyl group, suggesting 5 and 7 to be two isomer forms of citrusin [19]. Compound 10 (tR = 48.4 min) was revealed as formate adduct [M+HCOO] − at m/z 515, which fragmentation generated a base ion peak at m/z 469 due to the loss of a formic acid, thus was tentatively identified as limonin [14].…”
Section: Legal Quality Parametersmentioning
confidence: 99%